Authors (The Biblical archaeology review, 2021)
Elizabeth H.P. Backfish (Not Lost in Translation: Hebrew Wordplay in Greek) is Associate Professor in the School of Theology and Leadership at William Jessup University. Her recent book is Hebrew Wordplay and Septuagint Translation Technique in the Fourth Book of the Psalter (2019).